Subject Files Relating to the USSR
The files contain mostly newspaper clippings from western press sources, news agency releases but also brochures on Agriculture, Economic Conditions and Policy, Intellectual life, Population, Prisons and Youth. Of particular interest are files on Concentration Camps, Human Rights, Foreign Policy: Middle East, Minorities, Missile Program and Resistance and Dissidents. Accruals not expected